Development of a prototype for the treatment of ater contaminated with glyphosate - Santos, Julio Cesar Maciel; Rubio, Andressa Jenifer; Sousa, Jean Carlos Araujo de; Almeida, Ana Carolynna Severo; Bergamasco, Rosângela; Yamaguchi, Natália Ueda (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
One of the current challenges is to meet the demands for quality water since the contamination of bodies of water has been intensified in the last years with the increase in the use of pesticides. Therefore, finding a way to remove contamination by pesticides from water becomes a relevant work. In this study, it was presented the design and construction of a pilot-scale batch reactor prototype in order to remove the herbicide glyphosate from artificially contaminated water using a graphene hybrid composite with manganese ferrite, MnFe2O4-G, as an adsorbent. For the reactor design, it was initially required to know the steps necessary for the removal of the glyphosate from water, according to the chosen hybrid compound for the removal. After the steps were determinated, the components were selected to compose the treatment system. The layout of the prototype was defined and the positions of the elements and materials were chosen. Finally, the prototype was built and tested in the laboratory. The results showed that within 15 minutes the separation was completed and 70% of the adsorbent was recovered in the magnetic separator after 4 complete cycles of treatment. It was concluded that the prototype built fulfills the objective for which it was proposed, presenting the advantage of having all the steps of adsorption and desorption for glyphosate decontamination in the same equipment, being able to be expanded for use in effluent treatment plants.